Intraoperative factors associated with delayed recovery of liver function after hepatectomy: analysis of 1969 living donors. Issue 2 (10th September 2015) - Choi, S.‐S.; Cho, S.‐S.; Ha, T.‐Y.; Hwang, S.; Lee, S.‐G.; Kim, Y.‐K.
Abstract : Background: The safety of healthy living donors who are undergoing hepatic resection is a primary concern. We aimed to identify intraoperative anaesthetic and surgical factors associated with delayed recovery of liver function after hepatectomy in living donors. Methods: We retrospectively analysed 1969 living donors who underwent hepatectomy for living donor liver transplantation. Delayed recovery of hepatic function was defined by increases in international normalised ratio of prothrombin time and concomitant hyperbilirubinaemia on or after post‐operative day 5. Univariate and multivariate logistic regression analyses were performed to determine the factors associated with delayed recovery of hepatic function after living donor hepatectomy. Results: Delayed recovery of liver function after donor hepatectomy was observed in 213 (10.8%) donors. Univariate logistic regression analysis showed that sevoflurane anaesthesia, synthetic colloid, donor age, body mass index, fatty change and remnant liver volume were significant factors for prediction of delayed recovery of hepatic function. Multivariate logistic regression analysis showed that independent factors significantly associated with delayed recovery of liver function after donor hepatectomy were sevoflurane anaesthesia (odds ratio = 3.514, P < 0.001), synthetic colloid (odds ratio = 1.045, P = 0.033), donor age (odds ratio = 0.970, P = 0.003), female gender (odds ratio = 1.512, P = 0.014) and remnant liver volume (odds ratio = 0.963, P < 0.001). Conclusions: Anaesthesia with sevoflurane was an independent factor in predicting delayed recovery of hepatic function after donor hepatectomy. Although synthetic colloid may be associated with delayed recovery of hepatic function after donor hepatectomy, further study is required. These results can provide useful information on perioperative management of living liver donors.